INCREASING STUDENTS ' INTEREST IN FOLK APPLIED ARTS (Academia Science Repository, 2023)
This article reveals a number of ways to increase students ' interests in folk applied art. It is included to instill the essence of art in the minds of children , to conduct conversations and discussions about works of art that are interesting.